The 15-K neutron structure of saccharide-free concanavalin A - Blakeley, M. P. (National Academy of Sciences, 2004)
The positions of the ordered hydrogen isotopes of a protein and its bound solvent can be determined by using neutron crystallography. Furthermore, by collecting neutron data at cryo temperatures, the dynamic disorder within a protein crystal is reduced, which may lead to improved definition of the nuclear density. It has proved possible to cryo-cool very large Con A protein crystals (>1.5 mm(3)) suitable for high-resolution neutron and x-ray structure analysis. We can thereby report the neutron crystal structure of the saccharide-free form of Con A and its bound water, including 167 intact D(2)O molecules and 60 oxygen atoms at 15 K to 2.5-Å resolution, along with the 1.65-Å x-ray structure of an identical crystal at 100 K. Comparison with the 293-K neutron structure shows that the bound water molecules are better ordered and have lower average B factors than those at room temperature. Overall, twice as many bound waters (as D(2)O) are identified at 15 K than at 293 K. We note that alteration of bound water orientations occurs between 293 and 15 K; such changes, as illustrated here with this example, could be important more generally in protein crystal structure analysis and ligand design. Methodologically, this successful neutron cryo protein structure refinement opens up categories of neutron protein crystallography, including freeze-trapped structures and cryo to room temperature comparisons.